2007
DOI: 10.1111/j.1365-2486.2007.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 balance of boreal, temperate, and tropical forests derived from a global database

Abstract: Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
856
16
30

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 930 publications
(975 citation statements)
references
References 61 publications
73
856
16
30
Order By: Relevance
“…In this study, we initially found that the spatial variations in GPP and RE are commonly controlled by MAT, MAP, and EVI (Table 3). The controls of temperature and precipitation on the spatial variations in GPP and RE are similarly reported in China , Asian Hirata et al, 2008), European, and American regions Luyssaert et al, 2007;Reichstein et al, 2007b). Furthermore, we found that GPP and RE responded to the common climatic and vegetation factors in a parallel way across The framework illustrates that GPP and RE show similar responses to the spatial variations in environmental conditions (such as MAT and MAP) (panel.a1) and ecosystem traits (EVI) (panel.b1).…”
Section: Underlying Mechanisms For the Covariation Between Gpp And Rementioning
confidence: 72%
See 1 more Smart Citation
“…In this study, we initially found that the spatial variations in GPP and RE are commonly controlled by MAT, MAP, and EVI (Table 3). The controls of temperature and precipitation on the spatial variations in GPP and RE are similarly reported in China , Asian Hirata et al, 2008), European, and American regions Luyssaert et al, 2007;Reichstein et al, 2007b). Furthermore, we found that GPP and RE responded to the common climatic and vegetation factors in a parallel way across The framework illustrates that GPP and RE show similar responses to the spatial variations in environmental conditions (such as MAT and MAP) (panel.a1) and ecosystem traits (EVI) (panel.b1).…”
Section: Underlying Mechanisms For the Covariation Between Gpp And Rementioning
confidence: 72%
“…GPP represents the gross CO 2 uptake through photosynthesis by all plants at the ecosystem level (Chapin et al, 2002;Luyssaert et al, 2007). RE is the gross CO 2 release from the ecosystem through both autotrophic respiration (R a ), which provides energy for the growth and maintenance of foliage, wood, and roots (Chapin et al, 2002;Waring et al, 1998), and heterotrophic respiration (R h ), which derives from the process of decomposition through microbial activities (Luyssaert et al, 2007). Understanding the variations in GPP and RE and their relationships is helpful for better understanding the terrestrial carbon cycle and predicting the global carbon budget.…”
Section: Introductionmentioning
confidence: 99%
“…Current soil respiration estimates neglect the C released to inland waters. A downward revision of the estimate of soil heterotrophic respiration to account for the soil C channelled to inland freshwater systems would nevertheless remain within the uncertainty of this flux 32 .…”
Section: Contemporary Estimates Of Lateral Carbon Fluxesmentioning
confidence: 99%
“…We followed the same procedure as with the NPPpot assessment, using three global biome maps 31,42,43 . We used various databases for potential carbon stocks in vegetation 4,16,[60][61][62][63] Table 5 shows potential vegetation units and the potential carbon stock values assigned, and Supplementary Tables 8-12 show results from forest site-data studies that explicitly discern natural from managed forests 32,33 . A comparison of these data reveals that the data we use are well in line with the site-specific studies 36,37 .…”
Section: Npp Of the Actual Vegetation (Nppact )mentioning
confidence: 99%